2016
DOI: 10.1037/adb0000231
|View full text |Cite
|
Sign up to set email alerts
|

Association between smoking-related attentional bias and craving measured in the clinic and in the natural environment.

Abstract: Link to publication record in Explore Bristol Research PDF-document This article may not exactly replicate the final version published in the APA journal. It is not the copy of record. This is the accepted author manuscript (AAM). The final published version (version of record) is available online via American Psychological Association at http://www.apa.org/pubs/journals/adb/index.aspx. Please refer to any applicable terms of use of the publisher. University of Bristol -Explore Bristol Research General rightsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Future ecological studies are needed to more strictly probe incentive sensitization mechanisms in LS drinkers. It will be important to determine whether similar findings are observed when participants explicitly report noticing alcohol cues (e.g., Begh, et al, 2016) or when cue presentations are manipulated directly via the mobile device (e.g., Wray, Godleski, & Tiffany, 2011).…”
Section: Discussionmentioning
confidence: 93%
“…Future ecological studies are needed to more strictly probe incentive sensitization mechanisms in LS drinkers. It will be important to determine whether similar findings are observed when participants explicitly report noticing alcohol cues (e.g., Begh, et al, 2016) or when cue presentations are manipulated directly via the mobile device (e.g., Wray, Godleski, & Tiffany, 2011).…”
Section: Discussionmentioning
confidence: 93%
“…This suggests that rather than being a stable trait between smoking groups, it fluctuates with the incentive value of a cue which makes within-group differences more important. Initial support for this theory was provided by Begh, Smith and Ferguson (2016) who found that laboratory measures of attentional bias such as the Stroop task and the visual probe task did not predict subsequent smoking behaviour in the real-world. However, assessments of craving and awareness of smoking cues in the environment measured through ecological momentary assessment did predict subsequent smoking behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Investigating how attentional bias fluctuates was not within the scope of these studies, meaning direct support for this theory had to be provided by other research. Begh et al (2016) found that measuring attentional bias in the lab as a trait-level construct did not predict subsequent smoking behaviour, but short-term craving and evaluation of drug-cues through ecological momentary assessment did.…”
Section: Attentional Bias In Daily and Non-daily Smokersmentioning
confidence: 92%
“…Next, participants reported exposure to smoking cues, attention to smoking, and craving for cigarettes in the field. Yet, Begh et al [25] found no association between attentional biases and neither of the EMA variables. Groefsema et al [26] used a stimulus-response-compatibility task and a visual probe task in the laboratory to measure approach and attentional biases.…”
Section: Mobile Data Collection Of Behavioral Tasks In Substance Use ...mentioning
confidence: 99%